Uses of medicinal plants by Haitian immigrants and their descendants in the Province of Camagüey, Cuba - Barreto Adelaida; Beyra Angela; Godínez Daimy; Volpato Gabriele (BMC, 2009)
Abstract Background Haitian migrants played an important role shaping Cuban culture and traditional ethnobotanical knowledge. An ethnobotanical investigation was conducted to collect information on medicinal plant use by Haitian immigrants and their descendants in the Province of Camagüey, Cuba. Methods Information was obtained from semi-structured interviews with Haitian immigrants and their descendants, direct observations, and by reviewing reports of traditional Haitian medicine in the literature. Results Informants reported using 123 plant species belonging to 112 genera in 63 families. Haitian immigrants and their descendants mainly decoct or infuse aerial parts and ingest them, but medicinal baths are also relevant. Some 22 herbal mixtures are reported, including formulas for a preparation obtained using the fruit of Crescentia cujete. Cultural aspects related to traditional plant posology are addressed, as well as changes and adaptation of Haitian medicinal knowledge with emigration and integration over time. Conclusion The rapid disappearance of Haitian migrants' traditional culture due to integration and urbanization suggests that unrecorded ethnomedicinal information may be lost forever. Given this, as well as the poor availability of ethnobotanical data relating to traditional Haitian medicine, there is an urgent need to record this knowledge.